2018
DOI: 10.1002/jssc.201800796
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of solid‐phase extraction of parabens and benzophenones in water samples using a combination of Plakett‐Burman and Box‐Behnken designs

Abstract: An automated method for the analysis of methylparaben, propylparaben, benzophenone‐3, and benzophenone‐4 in water effluents via on‐line solid‐phase extraction coupled with high‐performance liquid chromatography/ultraviolet detection was proposed. The preconcentration parameters were studied using Plackett‐Burman and Box‐Behnken experimental designs using a C18 sorbent material. The results demonstrated that the eluent volume, composition, and sorbent amount were statistically significant. Optimal conditions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Mean values of 6.3 and 3.8 (p > 0.05) were obtained for the lack-of-fit test, suggesting that the model is reliable in predicting the response and that it can predict variations within the response [37]. Figures 1 and 2 confirm that the curve of observed values as a function of predicted values perfectly fits the shape of a straight line; we note the close agreement that exists between the experimental results and the theoretical values predicted by the polynomial model [40][41][42][43][44].…”
Section: Model-fitting and Statistical Analysissupporting
confidence: 55%
“…Mean values of 6.3 and 3.8 (p > 0.05) were obtained for the lack-of-fit test, suggesting that the model is reliable in predicting the response and that it can predict variations within the response [37]. Figures 1 and 2 confirm that the curve of observed values as a function of predicted values perfectly fits the shape of a straight line; we note the close agreement that exists between the experimental results and the theoretical values predicted by the polynomial model [40][41][42][43][44].…”
Section: Model-fitting and Statistical Analysissupporting
confidence: 55%
“…There is only a 4.71% chance that an F-value this large could occur due to noise. The results demonstrated that the model was significant, as evidenced by the high value of the F-test and a low p -value [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the development of a SPE procedure for the pre-concentration of analytes in water samples requires the study of the effect of several parameters on the retention/elution of these analytes on the SPE sorbent. Optimization of these parameters can be performed using step-by-step and/or multifactorial experimental design methodologies, being the last approach particularly useful for the pre-concentration of multiclass analytes [45][46][47][48]. In general, step-by-step optimization approach is employed to determine the optimal conditions for independent parameters (e.g.…”
Section: Solid-phase Extraction Optimizationmentioning
confidence: 99%